2020
DOI: 10.1158/1535-7163.mct-19-0611
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Sulforaphane-Regulated Gene Network in Suppression of Breast Cancer–Induced Osteolytic Bone Resorption

Abstract: Bone is the most preferred site for colonization of metastatic breast cancer cells for each subtype of the disease. The standard of therapeutic care for breast cancer patients with bone metastasis includes bisphosphonates (e.g., zoledronic acid), which have poor oral bioavailability, and a humanized antibody (denosumab). However, these therapies are palliative, and a subset of patients still develop new bone lesions and/or experience serious adverse effects. Therefore, a safe and orally bioavailable interventi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…This growth inhibition involved G 2 /M cell cycle arrest, consistent with reported observations in acute lymphoblastic leukemia, ovarian cancer and colon cancer [15,47,48]. G 2 /M cell cycle arrest is a checkpoint induced by DNA damage that is controlled by a p21/cdc2/cyclin B1 [15,21,28]. In endometrial cancer cell lines, sulforaphane induced phosphorylation of cdc2 on Tyr15, which is consistent with inhibition of the p21/cdc2/cyclin B1 complex driving G2/M progression.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This growth inhibition involved G 2 /M cell cycle arrest, consistent with reported observations in acute lymphoblastic leukemia, ovarian cancer and colon cancer [15,47,48]. G 2 /M cell cycle arrest is a checkpoint induced by DNA damage that is controlled by a p21/cdc2/cyclin B1 [15,21,28]. In endometrial cancer cell lines, sulforaphane induced phosphorylation of cdc2 on Tyr15, which is consistent with inhibition of the p21/cdc2/cyclin B1 complex driving G2/M progression.…”
Section: Discussionsupporting
confidence: 88%
“…The chemopreventive and therapeutic effects of sulforaphane have been comprehensively investigated in various cancers in vitro and in vivo [17]; however, it has not yet been studied in endometrial cancers. The safety of sulforaphane and sulforaphane-rich broccoli sprout extract (sulforaphane-BSE) has been tested clinically [20,21], and multiple phase I and phase II trials have been completed evaluating the efficacy of sulforaphane amongst patients with prostate cancer and breast cancer. These promising activities suggest that sulforaphane may also have value for use in endometrial cancer treatment regimens.…”
Section: Introductionmentioning
confidence: 99%
“…The cell cycle arrest at the G2/M phase is a DNA damage checkpoint controlled by p21/cdc2/cyclin B1. 34 In EC cell lines, OSU-03012 induced P21 upregulation, which is consistent with the inhibition of the p21/cdc2/cyclin B1 complex responsible for G2 to M cell cycle regulation.…”
Section: Discussionsupporting
confidence: 65%
“…As a pleiotropic compound, SFN is known to protect cells from deoxyribonucleic acid (DNA) damage and to modulate cell proliferation, apoptosis, angiogenesis, invasion, and metastasis in cancer [ 21 , 22 , 23 , 24 ]. Recently, it was reported that SFN could also be used to treat diseases associated with pathological bone resorption, such as bone metastasis in breast cancer, osteoporosis, and osteoarthritis [ 25 , 26 , 27 ]. In addition, Tomohiro Takagi et al suggested that SFN plays a negative role in RANKL-induced osteoclastogenesis, but the underlying mechanisms need to be further investigated [ 10 , 28 ].…”
Section: Discussionmentioning
confidence: 99%